Modi gambit: Decording Modi 2.0 - Verma, Sanju (New Delhi Gaurav book, 2021)
This book talks at length about various milestones achieved in last two years of Prime Minister Narendra Modi's remarkable, second term at the helm.Path breaking reforms like labour code,banking consolidation,denationalisation of coal, making of a V-shaped recovery,the PLI scheme,eRUPI,Gatishakti Masterplan, privatisation of Air India,unrelenting fight against Covid and ofcourse,historic milestone of crossing a billion doses,under world's largest vaccination drive,reflect PM Modi's resolute determination. Abrogation of Article 370,Ram Mandir verdict,banning instant triple talaq,QUAD summit,victories in Bihar &Assam,massive seat-share rise in West Bengal,National Education Policy and ofcourse,PM Modi's massive contribution to climate justice,have been discussed threadbare. The Congress Party,ruled India for decades together but even basics like toilets,sanitation facilities,uninterrupted electricity and access to banking facilities,remained a mirage. Prime Minister Modi's biggest legacy is the incorruptible nature of his government,where tolerance for corruption is zero. Introduction of the book has been written by one of the tallest leaders in the Bharatiya Janata Party (BJP),B.L.Santhosh,who is the National General Secretary (Organisation),of the BJP. Foreword has been written by the erudite,Padma Shri,Mohandas Pai,while Afterword has been written by ace journalist, Anand Narasimhan,Managing Editor at CNN News 18. The book has some very interesting takes on Modi 2.0 by Padma Shri, Dr. Sanjeev Bagai and one of India's most reputed wealth managers,Porinju Veliyath, who also shares his insights on PM Modi's path breaking work. Apart from the fearless journalist and now entrepreneur,Rohan Dua, Testimonials from Padma Bhushan,Dr. Devi Prasad Shetty and Ashish Chauhan,CEO of Bombay Stock Exchange,are worth a read and endorse the brilliant work done by the author,Sanju Verma,in capturing every mega achievement of Modi 2.0.
Keywords: Prime minister; Indian Politics